2021
DOI: 10.1098/rstb.2019.0736
|View full text |Cite
|
Sign up to set email alerts
|

Molecular regulation of lifespan extension in fertile ant workers

Abstract: The evolution of sociality in insects caused a divergence in lifespan between reproductive and non-reproductive castes. Ant queens can live for decades, while most workers survive only weeks to a few years. In most organisms, longevity is traded-off with reproduction, but in social insects, these two life-history traits are positively linked. Once fertility is induced in workers, e.g. by queen removal, worker lifespan increases. The molecular regulation of this positive link between fecundity and longevity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 80 publications
3
49
1
Order By: Relevance
“…Several studies have shown that reproductives live longer than non-reproductives even when they do not differ in ontogeny and morphology, e.g. as in certain species of ants [34,56,57] and reproducing workers of honeybees [58] and ants [37,40,43]. Similarly, highly fecund queens of Cardiocondyla ants live longer than queens that lay only a few eggs per week [59].…”
Section: Discussion (A) Remoulding Longevity and Fecundity In Social mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that reproductives live longer than non-reproductives even when they do not differ in ontogeny and morphology, e.g. as in certain species of ants [34,56,57] and reproducing workers of honeybees [58] and ants [37,40,43]. Similarly, highly fecund queens of Cardiocondyla ants live longer than queens that lay only a few eggs per week [59].…”
Section: Discussion (A) Remoulding Longevity and Fecundity In Social mentioning
confidence: 99%
“…As Negroni et al [43] show, workers of the ant Temnothorax rugatulus, which laid eggs over several months under queenless conditions, do not readily revert to their previous non-reproductive physiology when re-joined with the queen: their transcriptomes suggest that, while their fecundity goes down, they still show signs of increased longevity. In this case, lifespan extension and fertility appear to be reversible only to some extent.…”
Section: Contributionsmentioning
confidence: 99%
“…Reproduction has strong effects on the physiology and immunity of workers, who can become more resistant to oxidative stress and often live longer (dos Santos Conceição Lopes, Campbell, & Contrera, 2020;Kohlmeier et al, 2017;Majoe, Libbrecht, Foitzik, & Nehring, 2021;Negroni, Segers, Vogelweith, & Foitzik, 2020). These positive effects of reproduction have been linked to the activation of signaling pathways such as insulin/insulin-like growth factor (IIS), the target of rapamycin (mTOR), and the alpha-ketoglutarate (alpha-KG) (Negroni, Macit, Stoldt, Feldmeyer, & Foitzik, 2021). Indeed, gene expression changes profoundly in workers after queen loss in social wasps (Taylor, Cini, Sumner, Wyatt, & Reuter, 2021), honeybees (Cardoen et al, 2011), and ants (Negroni et al, 2021;Wurm, Wang, & Keller, 2010) and in various tissues from the brain to the fat body.…”
Section: Introductionmentioning
confidence: 99%
“…These positive effects of reproduction have been linked to the activation of signaling pathways such as insulin/insulin-like growth factor (IIS), the target of rapamycin (mTOR), and the alpha-ketoglutarate (alpha-KG) (Negroni, Macit, Stoldt, Feldmeyer, & Foitzik, 2021). Indeed, gene expression changes profoundly in workers after queen loss in social wasps (Taylor, Cini, Sumner, Wyatt, & Reuter, 2021), honeybees (Cardoen et al, 2011), and ants (Negroni et al, 2021;Wurm, Wang, & Keller, 2010) and in various tissues from the brain to the fat body. Similarly, gene expression differs between reproductive and sterile bumblebee workers (Marshall, Lonsdale, & Mallon, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation